National Health Insurance (JKN) Rights After Termination of Employment (PHK): Case Study of PT. FI - Fauzan Alsadilla Hermawan; Muthia Sakti; Iwan Erar Joesoef (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the fulfillment of National Health Insurance Rights (JKN) for workers who experience Termination of Employment (PHK) at PT. FI and evaluate the regulation of JKN rights after layoffs that provide justice for workers. The method used is normative legal research with a qualitative approach, which includes the selection and classification of legal materials as well as normative analysis of relevant regulations. Based on field findings, this study shows that there are administrative errors in reporting the status of layoffs that cause delays in fulfilling health insurance rights for laid-off workers. In addition, this study also found that even though the post-layoff JKN regulation has been regulated in the law, improper implementation can hinder the granting of rights fairly. This study recommends simplifying reporting procedures, increasing supervision by BPJS Kesehatan, and further education for companies to avoid administrative errors. Thus, this study contributes to the understanding of the importance of social justice in regulating health insurance for laid-off workers.